Control of transcription processivity in phage lambda: Nus factors strengthen the termination-resistant state of RNA polymerase induced by N antiterminator. - DeVito, J (1994)
During transcription of phage lambda early operons, the N gene product alters host RNA polymerase (RNAP) so that transcription proceeds through multiple stop signals. Here, we reproduce the essence of N activity with purified components in synthetic transcription units that contain lambda pL promoter and the N-recognition site, nutL, followed by a variety of intrinsic terminators. We show that three host factors (NusA, NusE, and NusG) are essential for N to allow appreciable transcription through multiple terminators and that this persistent antitermination is stimulated by a fourth factor, NusB. Remarkably, in the absence of all four factors, N suppresses various terminators placed near the nut site. This basal antitermination activity of N is enhanced by NusA and is diminished by high salt and temperature. We postulate that N interacts with RNAP directly, inducing the termination-resistant state. While NusA facilitates this interaction, the other factors strengthen it sufficiently over time and distance so that RNAP bypasses multiple terminators. The dispensability of NusB for persistent antitermination in vitro, but not in vivo, raises the possibility that NusB performs two functions: it increases the stability of N antitermination complex and also counteracts an inhibitory factor in the cell.